2017
DOI: 10.4236/ce.2017.815165
|View full text |Cite
|
Sign up to set email alerts
|

Learning High School Biology in a Social Context

Abstract: In this research, we developed a process that helped students connect cell and molecular biology concepts with problems in context of their lives. Specifically, we supplemented traditional teaching with problem, project and inquiry based laboratories, without changing the structure of the mandated biology curriculum. We ran the process twice, following the classroom based action research model. Our initial foray exhibited better student-developed projects and a modest improvement of test grades. Second time we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
1
0
1
Order By: Relevance
“…For instance, Tsai (2006) indicated that biological information was perceived by high school pupils as being less certain than knowledge in other science fields, like physics. In contrast, Basu et al (2017) found that most students believed that science was an impossible miracle that only highly qualified professionals could perform. The authors concluded that students' epistemic beliefs might have connection to their biology learning.…”
Section: Introductionmentioning
confidence: 88%
“…For instance, Tsai (2006) indicated that biological information was perceived by high school pupils as being less certain than knowledge in other science fields, like physics. In contrast, Basu et al (2017) found that most students believed that science was an impossible miracle that only highly qualified professionals could perform. The authors concluded that students' epistemic beliefs might have connection to their biology learning.…”
Section: Introductionmentioning
confidence: 88%
“…A falta de conexão da teoria com aplicações práticas dos conteúdos de biologia no ensino superior leva ao desinteresse dos alunos, comprometendo sua aprendizagem. Desta forma, vê-se como importante que o aluno tenha oportunidade de experimentar o mundo tangível durante as aulas, tornando-se protagonista do processo educativo no qual está inserido (Basu et al 2017).…”
Section: Análise Dos Questionáriosunclassified